Age and the u-shaped cost of job loss - Mehdi Bartal; Yvan Becard; Antoine Bertheau (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2025)
Job displacement causes large and persistent earnings losses. We document that these losses exhibit a U shape over the life cycle: young and old workers experience greater drops than mid-career workers. We develop a simple search model with human capital accumulation and deterioration that rationalizes this pattern. Losing a job early in the career is particularly costly because it implies missing out on fast wage growth opportunities. For older workers, specific human capital and firms' reluctance to hire explain most of the drop in earnings. Recessions affect the young disproportionately and exacerbate the U-shaped cost of job loss.
Keywords: E24; J24; J63; 330; Kündigung; Lohn; Altersgruppe; Humankapital; Arbeitsuche; Theorie; USA